Atypical Antipsychotic Induced Weight Gain in Schizophrenic Patients - Tetie Herlina; Dyah A. Perwitasari; Haafizah Dania; Santi Yuliani; Melisa I. Barliana (Indonesian Journal of Clinical Pharmacy, 2021)
Atypical antipsychotics are widely prescribed and have the potential to cause weight gain, which may result in the development of metabolic syndrome. Also, it is important to monitor the use of atypical antipsychotic for metabolic disturbance. The purpose of this study is to determine the side effects of atypical antipsychotics in increasing body weight in schizophrenia patients after 4 weeks of use. Furthermore, a retrospective design was conducted and data were collected based on consecutive sampling in 80 adult psychiatric inpatients (20 women and 60 men) with initial diagnoses of schizophrenia and with the same daily nutrition. The patients were hospitalized from January to March 2019, within the term (over 4 weeks) of initiation atypical antipsychotic. The patient body weight was collected before and 4 weeks after the treatment of atypical antipsychotic. The results showed that patients (20 women and 60 men) receiving atypical antipsychotic had a mean age of 35.6 years and a percentage of 70% women and 56% men had a weight gain of 1–5 kg over 4 weeks. The mean weight observed among our subjects increased from 57.55±10.743 kg to 59.83±12.205 kg after initiating treatment (p=0.001). However, the dual combination of atypical antipsychotics risperidone and clozapine are the most widely atypical antipsychotic used with a percentage equal to 91.25%, 3.75% clozapine, and 5% risperidone. Furthermore, it can be concluded that atypical antipsychotics use for at least 4 weeks can cause weight gain in schizophrenic patients. Pharmacist and doctors are recommended to monitor the metabolic side effects due to the atypical antipsychotic use. Keywords: Atypical antipsycotic, schizophrenia, weight gain  Antipsikotik Atipikal Menginduksi Peningkatan Berat Badan pada Pasien Skizofrenia AbstrakAntipsikotik atipikal banyak diresepkan dan berpotensi menyebabkan kenaikan berat badan yang dapat menyebabkan sindrom metabolik. Ada kebutuhan klinis yang mendesak untuk memantau penggunaan antipsikotik atipikal terhadap gangguan metabolisme. Penelitian ini bertujuan untuk mengetahui efek samping antipsikotik atipikal dalam meningkatkan berat badan pada pasien skizofrenia setelah pemakaian 4 minggu. Melalui desain retrospektif, data dikumpulkan dengan consecutive sampling pada 80 pasien rawat inap psikiatri dewasa (20 wanita dan 60 pria) dengan diagnosis awal skizofrenia dan dengan pengaturan nutrisi harian yang sama. Pasien dirawat di rumah sakit sejak Januari 2019 sampai dengan Maret 2019, dalam jangka menengah (lebih dari 4 minggu) pemberian antipsikotik atipikal. Data berat badan pasien dicatat sebelum dan 4 minggu sesudah pemakaian antipsikotik atipikal. Pasien (20 wanita dan 60 pria) yang menerima antipsikotik atipikal memiliki usia rata-rata 35,6 tahun, semua pasien dengan persentase 70% wanita dan 56% pria memiliki kenaikan berat badan 1–5 kg selama periode 4 minggu. Berat rata-rata yang diamati di antara subyek meningkat dari 57,55±10,743 kg menjadi 59,83±12,205 kg setelah memulai pengobatan (p=0,001). Antipsikotik atipikal yang paling banyak digunakan adalah kombinasi antipsikotik atipikal risperidon clozapin dengan persentase sebesar 91,25%, clozapin 3,75%, risperidon 5%. Kami menyimpulkan bahwa penggunaan antipsikotik atipikal selama setidaknya 4 minggu dapat menyebabkan penambahan berat badan pada pasien skizofrenia. Apoteker dan dokter direkomendasikan untuk memantau efek samping metabolik akibat penggunaan antipsikotik atipikal.Kata kunci: Antipsikotik atipikal, peningkatan berat badan, skizofrenia